Dynamic Analysis Method for Concurrency Bugs in Multi-process/Multi-thread Environments - Park, Jihyun; Choi, Byoungju; Jang, Seungyeun (International journal of parallel programming, 2020)
In this paper, we propose a method of analyzing the types and causes of concurrency bugs that can occur in multi-process/multi-thread environments by analyzing the information gathered in the execution environment. Our method reduces the false detection rate by employing a hooking technique that intercepts the software’s execution at runtime and reduces the overhead that can occur in the original software due to defect detection methods using optimized data collection. We implemented the proposed method as a tool and demonstrated its effectiveness by applying it to weapon system software that previously had concurrency bugs. In addition, the proposed method’s high performance was proven by applying it to software into which faults were injected and comparing the results with those obtained using other tools.